2017
DOI: 10.1007/s10792-017-0652-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of vision, patient satisfaction and long-term visual function after bilateral implantation of a low addition multifocal intraocular lens

Abstract: Our findings indicated that the Comfort IOL +1.5 D provides a good intermediate spectacle independence together with a high quality of vision, with a low amount of subjective symptoms and a contrast sensitivity similar to those obtained with a monofocal IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 22 publications
4
33
0
2
Order By: Relevance
“…It was reported that asymmetric multifocal IOLs with near addition of + 1.5 D yielded superb distance vision (UDVA of 0.00 logMAR and CDVA of − 0.08 logMAR) in conjunction with good intermediate vision (UIVA at 80 cm of 0.01 logMAR), but near vision was rather limited (UNVA at 40 cm of 0.41 logMAR) [ 2 ]. Another study indicated that Lentis Comfort LS-313 MF15 gave excellent distance and intermediate visual acuity (UDVA of − 0.01 logMAR and UIVA at 70 cm of 0.05 logMAR), while near visual acuity was at a lower level (UNVA at 30 cm of 0.54 logMAR) [ 4 ]. The findings of our study are in good agreement with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was reported that asymmetric multifocal IOLs with near addition of + 1.5 D yielded superb distance vision (UDVA of 0.00 logMAR and CDVA of − 0.08 logMAR) in conjunction with good intermediate vision (UIVA at 80 cm of 0.01 logMAR), but near vision was rather limited (UNVA at 40 cm of 0.41 logMAR) [ 2 ]. Another study indicated that Lentis Comfort LS-313 MF15 gave excellent distance and intermediate visual acuity (UDVA of − 0.01 logMAR and UIVA at 70 cm of 0.05 logMAR), while near visual acuity was at a lower level (UNVA at 30 cm of 0.54 logMAR) [ 4 ]. The findings of our study are in good agreement with these previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Contrast sensitivity function measured at 6 months postoperatively was within the normal range of age-matched controls. It has been shown that contrast sensitivity of this IOL is similar to that of standard monofocal IOLs [ 4 6 ]. Previous studies reported that the level of contrast sensitivity did not differ between extended-range-of-vision IOLs and monofocal IOLs, but these two IOLs exhibited significantly better level of contrast sensitivity than conventional multifocal IOLs with + 2.0 D or + 3.0 D addition [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extension to this trend are IOL described as 'Extended Depth of Focus' (EDOF). Designs include a low near addition (+1.75 D) (Gatinel and Loicq, 2016) diffractive IOL (Millan and Vega, 2017;Weeber et al, 2015) and asymmetric (+1.50 D) IOL (Pedrotti et al, 2018). The studies hitherto suggest it provides visual benefits across all distances after cataract surgery, with a minimal level of disturbing photic phenomena and high levels of patient satisfaction (Cochener and Concerto Study, 2016;Kaymak et al, 2016).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… 1–3 Currently, the majority of new generation MIOLs improve these defects and present a diffractive platform that splits lights to the retina, in order to obtain a good quality image at several distances and achieve a good spectacle independence. 4 5 Nowadays, modern MIOLs obtain multifocality, thanks to two different diffractive technologies which are extended range of vision (ERV) that is used by Tecnis Symfony and Enlighten technology (Enlighten Optical Technology) that is exploited by PanOptix. 6 7 Several studies have been carried out on these MIOLs, but the literature present discordant results on visual acuity at intermediate distances, defocus curve and on the quality of vision.…”
Section: Introductionmentioning
confidence: 99%